The development of high strength brazing technique for Ti-6Al-4V using TiZrCuNi amorphous filler - Jing,Y; Su,D; Yue,X; Britton,T; Jiang,J (Materials Characterization, 2017)
The brazing joint of the Ti-6Al-4V alloy was produced with a designed brazing filler alloy and the optimized brazing temperature which is lower than the β-phase transformation of the matrix. The strength and the ductility of brazing joined Ti-6Al-4V samples were evaluated by conventional tensile tests with a DIC 2D–strain field measurement. The Widmanstätten microstructure with no voids or cracks or intermetallic compounds was found throughout the joint with a width of β-lamellar as ~ 1 μm. Due to the fine acicular α-Widmanstätten and β-lamellar, and the uniformly diffused filler elements throughout the entire joint, the strength of the joint was as much as the matrix. In addition, the hardness test results agreed well with the tensile strength tests. All fractures occurred in the matrix rather than the brazing joints. Furthermore, the maximum local tensile strain was measured as 20% in the matrix, while under the same stress, the brazing joint only reached 6.3% tensile plastic strain. Thus, the mechanical properties of the joint with the associated microstructure demonstrated that a successful brazing filler alloy has been developed for the Ti-6Al-4V alloy.